Supraorbital foramen or notch and its relationship with the supraorbital nerve in human - Ferreira, Maria Rosana de Souza; Campina, Renata Cristinny de Farias; Magalhães, Carolina Peixoto; Valença, Marcelo Moraes (Headache Medicine, 2017)
Currently, interventions with anesthetic substances have been an alternative for headache treatment. There are some regions that are targeted for the application of anesthetics, such as the upper margin of the orbit, where two critical nerves, supratrochlear and supraorbital, pass. The objective of this study is to present some anatomical features characteristic of the superior orbital border and passage of the supraorbital nerve through a foramen or more often notch. Dry skulls from male and female individuals were used, measures were taken to compare the distance between the foramen and the median line of the skull. The length was measured and compared between the sexes, obtaining the following results in men (2.27 ± 0.29 cm) and women (2.18 ± 0.41 cm). The collected data are of extreme importance to understand the anatomy of the region and intervention in procedures of infiltrations and treatment of headache.